Perceptions of physical activity in preschool-aged children in urban and rural samples in South Africa - Stone, Matthew (Department of Psychology, 2016)
Physical activity has a well-established and beneficial role in physical, mental and social health. Early childhood is widely acknowledged as a formative and crucial stage of human development, both biologically and habitually. In South Africa, particularly, the direct health benefits of physical activity in this age group are under-emphasised in the policies and discourse around public health. There is evidence, however, that interventions in this age group can increase physical activity and decrease sedentary behaviour. In order to guide the development of such a programme, focus groups were conducted with parents and teachers across a range of socio-economic strata in various rural and urban communities in South Africa. These focus groups explored the perceptions surrounding physical activity, gross motor skills development and sedentary behaviour in children as well as identifying perceived barriers to physical activity. Physical activity was considered important for childhood development. Participants believed their children were physically active enough, although participants in higher socio-economic areas were concerned about the lure of technological devices. The perceived barriers in low socio-economic areas were predominantly the lack of safe spaces to play and resources, particularly human resources. It is recommended that training-focused programmes for teachers and activity based workshops are developed to promote physical activity taking into account these perceptions and barriers.